In Vitro and In Vivo Toxicity Studies on Cymbopogon giganteus Chiov. Leaves Essential Oil from Benin. (28th January 2020) - Toukourou, Habib; Uwambayinema, Francine; Yakoub, Yousof; Mertens, Birgit; Laleye, Anatole; Lison, Dominique; Quetin-Leclercq, Joelle; Gbaguidi, Fernand
Abstract : Cymbopogon giganteus Chiov. (Poaceae) is a medicinal plant used to treat various diseases in traditional medicine in several African countries. The present study aims to evaluate the oral and inhalation toxicity as well as the mutagenic effects of the essential oil of Cymbopogon giganteus leaves (EOCG) from a sample collected in Benin. Mutagenic potential was assessed by the Ames test using Salmonella typhimurium strains TA98 and TA100. Oral acute toxicity was carried out by administration of a single dose of 2000 mg/kg b.w. to Wistar rats while oral subacute toxicity was assessed by daily administration of 50 and 500 mg/kg of EOCG for 28 days. Finally, inhalation toxicity was assessed by administration of a single dose of 0.125%, 0.5%, 2% or 5% v/v of EOCG emulsions in 0.05% v/v lecithin solution in sterile water for the first experiment, and in a second one by administration of single dose of 0.125% or 0.5% v/v. A broncho-alveolar lavage was performed after 3 h or 24 h, respectively. The results show that EOCG is not mutagenic on Salmonella typhimurium strains at the highest concentration tested (200 μ g/plate). In the acute oral toxicity study, EOCG induce neither mortality nor toxicity, showing that the LD50 is greater than 2000 mg/kg. The subacute oral toxicity study at both doses did not show any significant difference in body weight, relative organ weight, hematological and/or biochemical parameters or histopathology as compared to the control group. EOCG induced mortality and inflammation in lungs 3 h after administration of a single dose of 5% or 2% v/v. Single doses of 0.125% or 0.5% v/v did not induce inflammation, cell recruitment nor cytotoxicity in lungs 3 h or 24 h after administration, suggesting safety at these concentrations. This first report on the in vivo toxicity will be useful to guide safe uses of EOCG.